Clinical Effect of Intravenous Vitamin C on Viral Myocarditis in Children: A Systematic Review and Meta-Analysis. (23rd April 2019) - Chen, Shuangdi; Zhao, Wenli; Zhang, Binjie; Jia, Yijun; Wu, Shihua; Zhong, Botao; Yu, Xuerong; Wang, Xueying; Hao, Yu; Wang, Hongwu; Zhao, Ye; Mizuno, Kaito; et al.
Abstract : Objective . To comprehensively compare the effects of conventional therapy combined with intravenous vitamin C and conventional therapy on viral myocarditis in children through a meta-analysis. Methods . Relevant articles including clinical trials of normal treatment combined with intravenous vitamin C and conventional therapy for viral myocarditis in children that were published between January 2000 and February 2018 were selected from PubMed, Cochrane Library, China National Knowledge Infrastructure, China Science and Technology Journal Database, and WANFANG database. The quality of the included studies was assessed using the Cochrane systematic review method (version 5.1.0); data quality was evaluated by two independent researchers. The total effective rate; LDH, CK, and CK-MB levels; and other indicators were analyzed using Rev Man 5.3 software. Results . Eight studies were eligible for this meta-analysis, which included a total of 426 patients in the treatment group and 363 patients in the control group. The meta-analysis results of six studies showed that the total effective rate of intravenous vitamin C combined with conventional therapy was higher than that of conventional therapy alone [Z = 5.46, 95% confidence interval (CI): 1.21 (1.13 to 1.30), P < 0.00001]; that of five studies showed that LDH levels were lower in children receiving intravenous vitamin C combined with conventional therapy than in those receiving conventional therapy alone [Z = 3.70, 95% CI: −1.88 (−2.88 to −0.88), P = 0.0002]; that of three studies showed that CK levels were lower in children receiving intravenous vitamin C combined with conventional therapy than in those receiving conventional therapy alone [Z = 4.21, 95% CI: −0.55 (−0.81 to −0.30), P < 0.0001]; that of four studies showed that CK-MB levels were lower in children receiving intravenous vitamin C combined with conventional therapy than in those receiving conventional therapy alone [Z = 13.64, 95% CI: −1.44 (−1.65 to −1.24), P < 0.00001]; that of two studies showed that CD3 levels were higher in children receiving intravenous vitamin C combined with conventional therapy than in those receiving conventional therapy alone [Z = 2.45, 95% CI: 0.41 (0.08–0.73), P = 0.01]; that of two studies showed no significant difference in changes in CD4 levels between children receiving intravenous vitamin C combined with conventional therapy and those receiving conventional therapy alone [Z = 0.28, 95% CI: −0.21 (−1.69 to 1.28), P = 0.78]; and that of two studies showed no significant difference in changes in CD4/CD8 between children receiving intravenous vitamin C combined with conventional therapy and those receiving conventional therapy alone [Z = 0.07, 95% CI: −0.03 (−0.73 to 0.67), P = 0.94]. Conclusion . The meta-analysis results showed that intravenous vitamin C combined with conventional therapy is better than the simple, conventional therapy for the treatment of viral myocarditis in children in terms of the total effective rate and LDH, CK, and CK-MB levels.